Participación Parental y Desarrollo Socio Emocional en Niños de 3 a 4 años de la Unidad Educativa “Dr. Reinaldo Espinosa Aguilar” 2023-2024 - Quiroga González, Valeria del Cisne (2024)
The present work on curricular integration entitled: Parental Participation and Socio-Emotional Development in Children from 3 to 4 years old from the “Dr. Reinaldo Espinosa Aguilar” 2023-2024; its central objective was to: Analyze parental participation and socio-emotional development in children aged 3 to 4 years from the “Dr. Reinaldo Espinosa Aguilar” during the period 2023-2024, in the theoretical framework a variety of topics related to parental participation and socio-emotional development were addressed. For this, descriptive research was carried out, with a non-experimental design and with a qualitative approach for the collection of information, a semi-structured interview was applied to two teachers and an observation sheet was applied to the boys and girls. The investigated population consisted of two teachers from the initial level I and initial level II and eighteen students. The main results obtained in the research show a low parental participation in the fulfillment of tasks sent by the teacher, and a low socio-emotional support in the boys and girls, while a small percentage of students have parental support, showing the fulfillment of their tasks and good behavior in a successful way. Therefore, it is concluded that parental participation in education is associated with better academic results, greater motivation for learning and is also the basis of vital interactions that concretize an upbringing that promotes socialization and the full development of personality and that acts in front of the child, as the most important dynamic agent that influences the socio-emotional formation and the structuring of social behaviors for life. Keywords: Parental Participation, Socio-Emotional, students, education